CONTINUING EDUCATION: WHERE DO WE GO? - Macazana Fernandez, Dante Manuel (2014)
In our context, continuous training of teachers is a priority to meet the needs of improving the quality of education. In this perspective , despite the socio-economic constraints that created the implementation of neoliberalism in our country poses a priority to find a new vision the social, cultural and economic development, from the reflections, consensus and redefinitions the teaching profession and its social function, and general education and society we need. A conception of the teacher must distinguish three dimensions: intellectual, educator and citizen, which are exercised in practice together and exert a reciprocal influence on each other. The teacher as an intellectual must be presented as a committed for the reproduction and development of culture, science, arts and humanities, and all kinds of cultural expression and the problems around them. This will allow the teacher to exercise its dimension as a teacher, studying and researching educational and pedagogical phenomena in different contexts facing reflecting and contributions of science and technology comprising performing critical assessments that allow rethink their practices and provide teachers. Also, the teacher as a citizen should be submitted as an active social actor and committed to the defense of public education, expressing a strong background of its public awareness and forming a vision of the future stars of national political life. In this sense the teacher, school and society should be a leader and motivating example for students to worry about social problems, the common good and values necessary to improve the quality of life in society. In this context and perspectives, governments and teachers unions are the ones to prioritize teacher training and pedagogical struggle, in order to contribute to better educational purposes , with a real remote school autonomy visions of privatization, with an educational community more reflective and committed to educational issues, with new pedagogical approaches of representative institutions, with continuous quality training based on reflections and ongoing research , and great knowledge of the context and the specificities of students.